Pengaruh Karakteristik Perusahaan Terhadap Intellectual Capital Disclosure (ICD) Pada Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia - Agung Sri Wardani (BIP's JURNAL BISNIS PERSPEKTIF, 2013)
The purpose of this paper is to examine the level of intellectual capital disclosure in annual report prepared by listed firms on IDX. This research examines influence between intellectual capital disclosure as a dependent variable and firm’s characteristic (industry type, leverage, ownership concentration, external auditor type, listing age, independent commissioner, audit committee size and firm’s size) as independent variables. This research used 105 annual reports 2010 of Indonesian listed firms. Sample was selected using purposive sampling method. The result shows that the average level of intellectual capital disclosure is only 35,86%. Multiple regression analysis is used to test the hypothesis. Statistical analysis demonstrates that audit committee size and firm’s size are significance to the level of intellectual capital disclosure.